International Financial Statistics, November 2018. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This November 2018 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. IFS, Balance of Payments Statistics, Direction of Trade Statistics, and Government Finance Statistics are available on CD-ROM by annual subscription. The CD-ROMs incorporate a Windows-based browser facility, as well as a flat file of the database in scientific notation. The country tables normally include data on a country's exchange rates, IMF position, international liquidity, monetary statistics, interest rates, prices, production, labor, international transactions, government accounts, national accounts, and population. Selected series, including data on IMF accounts, international reserves, and international trade, are drawn from the country tables and published in world tables as well. The monthly printed issue of IFS reports current monthly, quarterly, and annual data, while the yearbook reports 12 observations of annual data. In IFS, exchange rates are expressed in time series of national currency units per SDR and national currency units per US dollar, or vice versa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet